Molecular Signatures of Glacial Dissolved Organic Matter From Svalbard and Greenland. Issue 3 (13th March 2021) - Kellerman, Anne M.; Vonk, Jorien; McColaugh, Stephanie; Podgorski, David C.; van Winden, Elise; Hawkings, Jon R.; Johnston, Sarah Ellen; Humayun, Munir; Spencer, Robert G. M.
Abstract: Glaciers and ice sheets cover over 10 % of Earth's land surface area and store a globally significant amount of dissolved organic matter (DOM), which is highly bioavailable when exported to proglacial environments. Recent rapid glacier mass loss is hypothesized to have increased fluxes of DOM from these environments, yet the molecular composition of glacially derived DOM has only been studied for a handful of glaciers. We determine DOM composition using ultrahigh resolution mass spectrometry from a diverse suite of Arctic glacial environments, including time series sampling from an ice sheet catchment in Greenland (Russell Glacier) and outflow from valley glaciers in catchments with varying degrees of glacial cover in Svalbard. Samples from the Greenland outflow time series exhibited a higher degree of similarity than glacier outflow between glaciers in Svalbard; however, supraglacial meltwater samples from Greenland and Svalbard were more similar to each other than corresponding glacial outflow. Outflow from Russell Glacier was enriched in polyphenolic formulae, potentially reflecting upstream inputs from plants and soils, or inputs from paleosols overridden by the ice sheet, whereas Svalbard rivers exhibited a high level of molecular richness and dissimilarity between sites. When comparing DOM compositional analyses from other aquatic systems, aliphatic, and peptide‐like formulae appear particularly abundant in supraglacial meltwater, suggesting the DOM quickly metabolized in previous incubations of glacial water originates from energy‐rich supraglacial sources. Therefore, as glaciers lose mass across the region, higher‐quality fuel for microbial degradation will increase heterotrophy in coastal systems with ramifications for carbon cycling. Key Points: Dissolved organic matter (DOM) exhibits compositional variability in glacial outflow across Svalbard and Greenland Supraglacial DOM is compositionally similar across glaciers in Svalbard and Greenland but distinct from subglacial outflow Glacial DOM is uniquely enriched in aliphatic and peptide‐like organic matter compared to other aquatic systems